The Annual Cultivated Peanut (Arachis hypogaea L.) as a Potential Forage Crop for Livestock in the Southeastern U.S. - Robert O. Myer; Adegbola T. Adesogan; Ann R. Blount; Daniel W. Gorbet; Barry L. Tillman (EDIS, 2011)
AN255, a 5-page fact sheet by R. O. Myer, A. T. Adesogan, A. R. Blount, D. W. Gorbet, and B. L. Tillman, provides livestock producers with information on the use of annual cultivated peanut as a potential forage crop in the Southeast — forage production trial results, nutritional value, feeding value, and use as forage for grazing. Includes references. Published by the UF Department of Animal Sciences, December 2010.